ChemInform Abstract: Tissue Transglutaminase: An Emerging Target for Therapy and Imaging. Issue 9 (4th March 2014) - Pietsch, Markus; Wodtke, Robert; Pietzsch, Jens; Loeser, Reik
Abstract Review: 136 refs.